Tax Evasion in Chachapoyas: A Problem That the Ia Can Solve - Salazar, Carlos Alberto Hinojosa; Escobar, Benjamín Roldan Polo; Huamán, Sara Emilia Remuzgo; Reategui, Julio Arévalo; Zubiate, Franz Tito Coronel; Fernandez, Juan Manuel Buendia (International Journal of Membrane Science and Technology, 2024)
In a changing business environment, tax evasion poses a crucial challenge that impacts public finances and competitive equity. This study focuses on applying artificial intelligence in the tax management of micro and small enterprises (MSEs) in Chachapoyas, Peru, between 2018 and 2022. The objective of this study is to investigate how the application of artificial intelligence in the tax management of micro and small enterprises (MSEs) in Chachapoyas, Peru, can contribute to greater tax equity and strengthen corporate social responsibility, thus fostering a fairer and more supportive tax environment in the community. The proposed methodology involves collecting and analyzing the financial statements of micro and small enterprises (MSEs), as well as conducting interviews and questionnaires with their owners. It will focus on five specific objectives ranging from the identification of the causes of tax evasion to the evaluation of MSEs' willingness to adopt technologies in their tax management. In conclusion, promoting the adoption of artificial intelligence could strengthen trust in the tax system, increase tax collection for the common benefit and support the sustainable development of local businesses, generating a positive impact on the community and society as a whole.